Dosimetric properties of lthium aluminium borate glass doped with dysprosium oxide for ionizing radiation measurements - Aljewaw, Osama Bagi Mohamed (2022)
Thermoluminescence (TL) properties of glass dosimetry are known for their drawback, which is less sensitivity and a high fading effect. Hence, the purpose of this research is to investigate the influence of Dy3+ ion doped on the TL characteristics of Lithium Alumina Borate (LAB) glass, which was fabricated by using the melt quenching technique. The structures of 23Li2O - 7.5Al2O3 - (69.5-x) B2O3: x Dy2O3 glasses, with x = 0, 0.2, 0.4, 0.6, 0.8, 1, 1.5, 2, 2.5, and 3 mol% were studied by using X-ray diffraction (XRD) technique and Fourier Transform Infrared (FTIR) spectroscopy, where the samples of glass system were completely as an amorphous phase and showed the existence of BO3 and BO4 structural units. At room temperature, the photoluminescence (PL) emission spectra of the glass series at 350 nm exhibit two strong peaks located at 481 nm and 575 nm in the visible region, corresponding to the transitions 4F9/2 → 6H15/2 and 4F9/2 → 6H13/2, respectively. All the samples were irradiated at the Malaysia Nuclear Agency with the gamma-ray from Co-60 teletherapy. For undoped LAB glass, TL response and intensity were found to be very low and have no apparent curve compared with doped samples, which indicates the doping influence on the pure host glass. The optimum TL intensity was recorded with a heating rate of 10 ºC /s of doped the host glass samples. Thermal treatments at 300 ºC for 40 minutes were obtained for undoped and doped samples, respectively. The TL glow curves of LAB: Dy (0.8 mol%) revealed a single prominent peak at a maximum temperature (Tm) of 238 ºC. The dose-response of the glass of undoped shows a non-linearity effect; meanwhile, the doped glass (0.8 mol% of Dy) shows a good linearity on a dose range from 0.5 to 5 Gy gamma-ray with relative error values around 0.064% and 0.389%, respectively. Overall, the sensitivity of the undoped and optimum doped LAB glass was found about almost 0.607 and 12.530 (nC mg-1 Gy-1) with relative error values around 0.6% and 0.3%, respectively. The minimum detectable dose of the glass samples undoped and doped with 0.8 mol% Dy was found to be 1437.98 and 36.63 mGy with relative error values around 0.0431% and 4.463%, respectively. Reproducibility of the LAB glass samples exhibits undoped a high reproducibility of around 13.49% with relative error values of around 0.00891% and doped with 0.8 mol% Dy resulted in a low reproducibility to be 2.33% with relative error values of around 0.4 ± 0.2%, and Fading of LAB: 0.8 mol% Dy and undoped glass are found almost 15% and 9% over the time 627 hours with relative error values around 0.3 ± 0.1%. LAB: undoped and 0.8 mol% Dy doped glasses were found to have a good Zeff = 7.34 and 10.59 of tissue and bone biological human, respectively, which best implies passive dose measurement. Other TL kinetic parameters such as activation energy (E) and escape frequency factor (s) for the glass samples were found as 0.527 eV and 7.14 × 107 s-1, also optimized for dosimetry and validated by Chen’s method. Hence, the study ascertained that the optimized TL glass LAB: Dy (0.8 mol%) has the potential to be used for passive dose monitoring.